Immediate implant placement in anterior teeth with grafting material of autogenous tooth bone vs xenogenic bone - Dong Wu; Lin Zhou; Jichao Lin; Jiang Chen; Wenxiu Huang; Yonghui Chen (BMC, 2019)
Abstract Background The aim of the study was to compare the efficacy of the autogenous tooth bone and xenogenic bone grafted in immediate implant placement with bone defect. Methods Thirty patients whose compromised anterior teeth need immediate implant placement were enrolled. Autogenous tooth bone made from the extracted teeth by chair-side or the xenogenic bone were used to repaired bone defect. Clinical examination, radiographic assessment about the horizontal bone change in the level of 0 mm, 3 mm and 6 mm below the implant neck and the marginal bone loss were made immediately, 6 and 12 months after implant placement. Questionnaire of the feelings about the surgery were made at the time of removing the sutures. Results All implants achieved the success criteria without any complications at the follow-up period. The percent of the horizontal bone change and the marginal bone loss at 6 and 12 months were almost the same between two groups (P > .05). The horizontal bone loss at the first or the latter 6 months was almost the same (P > .05). But the horizontal bone loss at the 6 mm level was less than the 0 mm and 3 mm levels at 6 and 12 months (P < .05). Meanwhile patients seem more satisfied with the autogenous tooth bone derived from the questionnaire. Conclusion The bone volume change in the facial part of the implant after immediate placement is almost the same between two groups. Providing clinical evidence that the autogenous tooth bone made from compromised tooth can be an acceptable bone graft material.